(3TQM efXheI eMehO TGYQ aj GdBOGHs - (3eLghds
(3ChdgG (B:s
(3GdMeO ddg (B... (3EPG eG bdJ fGbdG aUMM abd Pdc ddebGHd jYfj cd eG PcQJg eQcHG eTJed Ydi GdfSHI GdJGeI GdNHQjI MGd chfc fGbdG dg dG eOYjG HfGA Ydi Cf egedGJ GdYdhe cdjGJ Ydi eG gh Gdefbhd (B...s
(3BNQgG (B:s
... (3hZf YhQVJ HGdJQcjH JefY HGf OYhi aj GdeOdhd MGUd Cj hEf YGQV GdebGHd Odjdc HGdJQcjH HCf bGd Odjdce hEf Od Ydi Gf GdcdGe UaI bOjeI dcf YfOfG eG jOd NdGag (B... (3JeJs
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdadSaI hGdefWbs